Situational influences on ethical sensemaking: Performance pressure, interpersonal conflict, and the recipient of consequences - Ness, A. M.; Connelly, S. (Human Performance, 2017)
Multiple situational influences are often present in organizational ethical dilemmas. This article explores the influences of recipient of the consequence, performance pressure, and interpersonal conflict on sensemaking processes, metacognitive reasoning strategies, and decision ethicality. Results suggest that decision ethicality is greater when individuals are the recipients of consequences. In addition, individuals analyzed causes of the dilemma to a greater extent when faced with low interpersonal conflict and when consequences occurred at an individual level. Individuals in the low interpersonal conflict condition anticipated consequences, looked within, and considered others more than those in the high interpersonal conflict condition. Additional research on performance pressure is needed given that the manipulation used in this study was not effective. Implications for theory and practice of ethics in organizational settings are discussed.